Reflections on critical uncertainties in biofutures - Taylor, Amos (ELS Publishing Co. Limited, 2025)
This paper reflects upon the concept of Critical Uncertainties, a term drawn from strategic foresight and risk management to identify issues that are highly uncertain and potentially highly impactful on a given strategic context. Given the daunting global challenges we face, the proposed biofutures associated with green transitions could be reimagined to encompass a broader spectrum of uncertainties, including existential risks and unknown unknowns. As global leadership acknowledges global risks, attention should be paid to how to engage these types of issues. This paper observes the participatory process of addressing and contextualising critical uncertainties and suggests that there may be a need for new frames. Planning for what is understood to be uncertain can be contrasted with the need for a new language of uncertainty that we do not yet contemplate. Low uncertainty issues may already be known, seen as sets of alternatives with direct implications, or then higher uncertainty involves even more complex fluid systems, and ultimately there is genuine uncertainty, which we cannot conceive. Within this context of utilising uncertainties, they are reflected upon through two key framings in this paper: imaginaries and future generations, both offering promising avenues for further exploration and inquiry of aspects of uncertainty. This reflexive text aims to reposition critical uncertainties for further study.